Soil Fertility Due to The Use of Inorganic Fertilizer In Batu Merah Village, Lampihong District - Alfi Maulana; Mulyawan, Ronny (SEAS (Sustainable Environment Agricultural Science), 2024)
The use of inorganic fertilizers in the short or long term to paddy soil can affect it as a source of soil nutrient availability. Knowing the status of soil fertility is for determining soil fertility status aimed at assessing soil characteristics and determining the main constraints of soil fertility for farming, determined by the physical, chemical and biological properties of the soil. Artificial (inorganic) fertilizers are fertilizers made in factories, inorganic fertilizers are formed by chemical processes. Inorganic fertilizers have advantages such as, made precisely and the administration can be adjusted. However, not all inorganic fertilizers contain complete elements (macro and micro), the administration can be combined with micro fertilizers and organic fertilizers. The method used in this research is descriptive quantitative. Soil sampling and analysis was carried out in March 2022, carried out diagonally at 5 sample points on the respondent's land, as many as 10 Siam Mutiara rice farmers, so that 50 sampling points were obtained. with an average land area of approx. (Â± 9.7 ha). The data obtained is presented in the form of tables or figures, then the data is described. The results of the analysis of the parameters of the chemical properties of the soil at the Laboratory of the Department of Soil Science, Faculty of Agriculture, University of Lambung Mangkurat, show the value of soil acidity (pH), acidic to very acid (3.95 - 4.89), C-organic (5.18%) - 15.52 %) is moderate to high. N-total (0.47% - 0.69%) value is moderate to high. P-total (12.48 mg/100 g - 118.83 mg/100 g) was rated very low to very high, and the K-total value (15.44 % - 43.05 %) was rated low to high.